Perioperative Intermittent Fasting Protects Ischemic Musculocutaneous Flap Tissue from Necrosis. Issue 5 (20th December 2022) - Weinzierl, Andrea; Harder, Yves; Menger, Michael D.; Laschke, Matthias W.
Abstract : Background: Dietary restriction, such as intermittent fasting (IF), has previously been shown to protect various tissues from ischemia-induced necrosis. Based on this finding, the authors herein evaluated for the first time the tissue-protective effects of IF in musculocutaneous flaps. Methods: Male C57BL/6N mice were randomly assigned to an IF group ( n = 8) and a control group with unrestricted access to standard diet ( n = 8). IF animals were put on a perioperative feeding schedule with 8 hours of unrestricted access to standard diet per day starting 7 days before flap elevation up to 3 days after surgery. Random pattern musculocutaneous flaps were raised and mounted into a dorsal skinfold chamber. Intravital fluorescence microscopy was performed on days 1, 3, 5, 7, and 10 after surgery for the quantitative assessment of angiogenesis, nutritive blood perfusion, and flap necrosis. After the in vivo observation period, the flaps were harvested for additional histologic and immunohistochemical analyses. Results: The authors found that the IF group exhibited more newly formed microvessels and a higher functional capillary density within the flap tissue when compared with controls. This was associated with a significantly lower rate of tissue necrosis. Immunohistochemical detection of different inflammatory cell subtypes revealed a markedly reduced number of invading myeloperoxidase-positive neutrophilic granulocytes in the musculocutaneous tissue of IF-treated animals. Conclusion: Considered together, these findings indicate that IF prevents flap necrosis by maintaining nutritive tissue perfusion and suppressing ischemia-induced inflammation. Clinical Relevance Statement: Given the frequent use of flaps in plastic surgery and the high rates of ischemic complications, any new approach to decrease such complications is clinically relevant.